ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI JAGUNG KOMPOSIT VAR. LAMURU (Zea mays) DI KELOMPOK TANI HIBIR PLITI DI DESA WAIRBLELER KECAMATAN WAIGETE KABUPATEN SIKKA - Fiator Nong (Jurnal Biogenerasi, 2026)
This study aims to analyze total production costs, determine revenue and net income, and assess farming efficiency and sustainability using the R/C ratio. A descriptive quantitative approach was employed, with purposive sampling for site selection and saturated sampling for respondents, involving all 21 members of the women farmer group. Data were collected through observation, interviews, and documentation. The results show that the average total fixed cost was IDR 191,431 and the average total variable cost was IDR 5,277,714, resulting in a total production cost of IDR 5,469,145 per season. Total revenue amounted to IDR 6,190,470 from an average production of 952.38 kg sold at a price of IDR 6,500 per kg, generating a net profit of IDR 721,325 per season. The R/C ratio of 1.131 indicates that corn farming is efficient, profitable, and feasible. Further Break-Even Point (BEP) analysis supports these findings, showing a production BEP of 0.199 kg, a revenue BEP of IDR 1,293.70, and a price BEP of IDR 5,742.560 per kg. Overall, this study concludes that corn farming is financially sound and suitable for continuation